Tapping on the chest of history : lost and found memories of Leopold Auenbrugger, inventor of percussion, in Austria and beyond - Borghi, Luca (Array, 2018)
Leopold Auenbrugger (1722-1809), the inventor of percussion, joins Rene Laennec as the father of modern physical examination. On the occasion of the bicentennial of the invention of the stethoscope (1816), I went in search of the material footprints left by Auenbrugger in his homeland, Austria. This attempt led me to construct a rather fragmented picture, with some disillusionment (e.g. about his tomb) and some pleasant surprise (e.g. a new interpretation of the extant iconography). Apparently, posterity has not been sufficiently mindful of or grateful towards this great innovator of medical science. All the more reason for knowing and protecting what is left of him: buildings, monuments, portraits… Anyway, Leopold Auenbrugger is honored and implicitly remembered today, as he was in the past, every time a doctor practices the percussion on the chest of a patient (i.e. billions of times each year).